If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9 + 9p = 10p Solving -9 + 9p = 10p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-10p' to each side of the equation. -9 + 9p + -10p = 10p + -10p Combine like terms: 9p + -10p = -1p -9 + -1p = 10p + -10p Combine like terms: 10p + -10p = 0 -9 + -1p = 0 Add '9' to each side of the equation. -9 + 9 + -1p = 0 + 9 Combine like terms: -9 + 9 = 0 0 + -1p = 0 + 9 -1p = 0 + 9 Combine like terms: 0 + 9 = 9 -1p = 9 Divide each side by '-1'. p = -9 Simplifying p = -9
| -4j+9=-3j | | 2(x+6)+3=5x-7 | | (3x+38)=5x | | 3x+14=-5x-17 | | 3x^9+39x^8+108x^7=0 | | 5-w=-16 | | 7x+10=-5x-16 | | 6x+6+2y=66 | | -5[x+6]=-5x+9 | | 12-21=-9 | | 3-6+2-1+8= | | 0.5x+3=2.5x-6 | | X-5+3x=6x-16 | | 3-3*6+2=l | | 2000=16t^2 | | .09k+13(k+300)=61 | | 2x-y=150 | | 2b+6.7=13.2-8b | | -37y=-36x+1 | | 9y=-4x+1 | | 6-k=7k-5k | | 25x-8=72 | | (180-x)=4x | | 4a=(180-x) | | e^2z+1=0 | | 6x*6xy= | | x^3-25x^2=15 | | 2f(3f+2)=3 | | -8x+8(1+4x)=152 | | 6xy+6x= | | 2c-6=2c+1 | | x^3-25*x^2=15 |